2010
DOI: 10.1093/ndt/gfq568
|View full text |Cite
|
Sign up to set email alerts
|

The increased risk of post-transplant diabetes mellitus in peritoneal dialysis-treated kidney allograft recipients

Abstract: Treatment by PD appears to be a possible novel factor, not yet reported, which may increase the risk of PTDM development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 14 publications
(15 reference statements)
0
17
0
Order By: Relevance
“…The eGFR was estimated by using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation [11]. Height and weight were measured on the day of surgery.…”
Section: Methodsmentioning
confidence: 99%
“…The eGFR was estimated by using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation [11]. Height and weight were measured on the day of surgery.…”
Section: Methodsmentioning
confidence: 99%
“…A relationship between CMV and Type 2 diabetes was first suggested three decades ago when researchers found CMV nucleic acids in 50% of pancreata from participants with Type 2 diabetes, but in only 2% of controls . In parallel, prospective studies of CMV and Type 2 diabetes in organ‐transplant recipients consistently reported a higher incidence of diabetes in CMV‐seropositive vs ‐seronegative recipients ; the odds ratio (OR) of new‐onset diabetes was 2.11 (95% CI 1.28 to 3.49), as reported in a meta‐analysis . Three epidemiological studies examined the CMV–diabetes association in the general population and found an increased prevalence of Type 2 diabetes associated with CMV seropositivity ; however, in two of them, the association was no longer statistically significant after adjustment for age and demographic factors .…”
Section: Introductionmentioning
confidence: 82%
“…A single center study reports on the occurrence of PTDM in 72 renal transplant recipients. In univariate analysis, the factors associated with the elevated risk of PTDM appearance were treatment by PD, older recipient age, positive family history of diabetes, hypertensive nephropathy as end-stage renal disease cause, higher body mass index at transplantation, and the graft from an older donor [28].…”
Section: Pd and Complications After Renal Transplantationmentioning
confidence: 99%